2022
DOI: 10.1177/02692155221083496
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical therapy given by telerehabilitation on pain and disability of individuals with shoulder pain: A systematic review

Abstract: Objective To systematically review the effects of physical therapy given by telerehabilitation on pain and disability in individuals with shoulder pain. Data sources PubMed, Embase, CINAHL, LILACS, Cochrane, Web of Science, SCOPUS, SciELO and Ibecs were searched in January/2022. Methods This systematic review followed PRISMA guidelines. Randomized controlled trials investigating the effects of physical therapy given by telerehabilitation on pain and disability in patients with shoulder pain were included. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…One of the most important and easy ways to gain healthy habits and keep all the body's systems, but perhaps the most important one, the immune system, is to exercise. In addition, considering these effects in the post-pandemic period, it is thought that online methods can continue to be used [ 3 , 4 ]. Another exercise method used as tele-exercise in the literature is Pilates [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important and easy ways to gain healthy habits and keep all the body's systems, but perhaps the most important one, the immune system, is to exercise. In addition, considering these effects in the post-pandemic period, it is thought that online methods can continue to be used [ 3 , 4 ]. Another exercise method used as tele-exercise in the literature is Pilates [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most telehealth modalities benefit people with musculoskeletal pain by improving pain and function and thus show potential to reduce the individual and societal burden imposed by musculoskeletal conditions. However, systematic reviews report the certainty of this evidence as low [8][9][10][11][12][13][14][15]. One important limitation is that most systematic reviews pooled results across a range of interventions (e.g., physical and psychological therapies, education, multimodal), so there is high clinical heterogeneity.…”
Section: Effectiveness Of Telehealth For Musculoskeletal Carementioning
confidence: 99%
“…Synchronous telerehabilitation may pose some limitations, particularly regarding the scalability of treatment and scheduling constraints, which has generated interest in asynchronous telerehabilitation. 17 Gava et al 18 conducted a systematic review focused on telerehabilitation in participants with shoulder pain, gathering evidence from six randomized controlled trials (RCTs) (1 synchronous + 5 asynchronous). The authors reported low to very low certainty of evidence supporting the use of telerehabilitation to improve pain and disability.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported low to very low certainty of evidence supporting the use of telerehabilitation to improve pain and disability. 18 …”
Section: Introductionmentioning
confidence: 99%